Turning the Page on Complex Texts : Differentiated Scaffolds for Close Reading Instruction (Grade-Specific Classroom Scenarios for Common Core State Standards). - Lapp, Diane (Solution Tree Press, 2016)
Ensure all learners become successful close readers. In this powerful resource, the authors examine what features make a text complex. Learn how to select appropriate complex texts and design instruction to meet the needs of every student. Explore grade-specific classroom scenarios that illustrate how to scaffold lessons to foster close reading and deepen comprehension at all stages of K-12 education. Benefits Gain practical teaching strategies for creating close reading lessons. Consider grade-level-specific instructional scenarios that illustrate how to support students' reading comprehensi.